Durable high-temperature alloy bar and preparation method thereof
By adjusting the element content and production process based on the existing high-temperature alloy materials, a new durable high-temperature alloy rod was prepared, which solved the problems of short service life, high cost and poor performance stability of existing materials, and achieved higher quality, longer life and wider application materials.
Patent Information
- Application Number
- CN202411816672.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-04
AI Technical Summary
The existing high-temperature alloy materials have short service life, high cost, poor performance stability, and cannot meet durability and use requirements in high-grade petroleum drill pipe applications.
A new durable high-temperature alloy rod material was prepared by adding a variety of different elements to the existing materials and adjusting the content, and combining with the existing production process for technical adjustments. The components of this material include C, Si, Mn, Al, Cr, Ni, Mo, La, Nb+Ta, Ti, Cu, O, H and other elements, and the specific content range is: C: 0.04-0.05%, Si: ≤0.15%, Mn: ≤0.25%, etc.
It has achieved new materials with more stable performance and better performance than existing alloy materials. The alloy rods produced have higher quality and accuracy, longer service life, more reliable durability and a wider range of use.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy materials, and in particular to a durable high-temperature alloy rod and a preparation method thereof. Background Art
[0002] High-grade oil drill pipes have strict requirements on strength, salt resistance, corrosion resistance, crack resistance and other properties when used. Existing high-temperature alloy materials have a relatively short service life when used in such products, and need to be replaced regularly during use. The cost during use is relatively high, and the performance stability in all directions is relatively poor. In order to solve the above problems, it is necessary to develop new high-temperature alloy materials to meet the durability and other use requirements of high-grade oil drill pipes. The company has previously developed an alloy material, but found that its performance stability is still not ideal during use, and it is necessary to re-develop its material composition. Summary of the invention
[0003] The purpose of the present invention is to provide a durable high-temperature alloy rod and a preparation method thereof. By conducting research and development on the basis of existing materials and re-adding a variety of different materials and combining them with different contents, a new material with more stable performance and various use performances superior to existing alloy materials can be obtained. Corresponding technical adjustments are made on the basis of the existing rod production process, so that alloy rod products with higher quality and precision can be produced. When used in the later stage, they can have more reliable durability and longer service life, and the processed products have higher quality and a wider range of use.
[0004] The technical solution of the present invention is as follows: A durable high temperature alloy bar, characterized by being composed of the following elements in percentage by weight: C: 0.04-0.05%; Si: ≤0.15%; Mn: ≤0.25%; S: ≤0.002%; P: ≤0.005%; Al: 0.250~0.75%; B: 0.003~0.035%; Cr: 17.0~21.0%; Ni: 50.0-55.0%; Mo: 2.8-3.3%; La: 0.040-0.050%; Nb+Ta:4.8-5.20%; Ti: 0.95-1.15%; Cu: ≤0.15%; O: ≤0.003%; H: ≤0.0012%; Co: ≤1.0%; the balance is iron and unavoidable impurities.
[0005] Further, C: 0.04%; Si: 0.12%; Mn: 0.25%; S: 0.002%; P: 0.005%; Al: 0.550%; B: 0.035%; Cr: 18.0%; Ni: 52%; Mo: 2.9%; La: 0.045%; Nb+Ta:4.8%; Ti: 1.15%; Cu: 0.15%; O: 0.003%; H: 0.0010%; Co: 1.0%.
[0006] Further, C: 0.05%; Si: 0.10%; Mn: 0.25%; S: 0.001%; P: 0.002%; Al: 0.450%; B: 0.003%; Cr: 21.0%; Ni: 55.0%; Mo: 3.1%; La: 0.045%; Nb+Ta:5.20%; Ti: 0.95%; Cu: 0.12%; O: 0.002%; H: 0.0012%; Co: 0.5%.
[0007] Further, C: 0.04%; Si: 0.15%; Mn: 0.15%; S: 0.002%; P: 0.002%; Al: 0.250%; B: 0.003%; Cr: 21.0%; Ni: 55.0%; Mo: 3.3%; La: 0.040%; Nb+Ta: 4.8%; Ti: 0.95%; Cu: 0.11%; O: 0.001%; H: 0.0012%; Co: 1.0%.
[0008] Step by step, C: 0.045%; Si: 0.15%; Mn: 0.15%; S: 0.002%; P: 0.003%; Al: 0.28%; B: 0.003%; Cr: 17.0%; Ni: 50.0%; Mo: 2.8%; La: 0.04%; Nb+Ta: 4.8%; Ti: 0.95%; Cu: 0.15%; O: 0.002%; H: 0.001%; Co: 1.0%.
[0009] A method for preparing a durable high-temperature alloy bar comprises the following steps: 1) raw material preparation, the raw materials are weighed according to the proportion content and then put into a smelting container and fully baked at 800°C for more than 4 hours, 2, the feed weight is greater than 20 tons; 2) medium frequency smelting, nickel-based materials are used to wash the furnace before the raw materials are added, the residual steel in the furnace is cleaned, the prepared raw materials are smelted and processed, slag deoxidation is performed in the later stage of smelting, the deoxidized slag is kept gray for more than 20 minutes, the refining temperature is 1550°C, the refining time is greater than 20 minutes, sampling and analyzing the composition and adjusting it within the qualified range, carbonization is increased to more than C0.8%, and the steel tapping temperature is greater than 16 00℃, the steel is poured into the AOD furnace; 3) AOD+LF refining is carried out, and crystalline silicon, fluorite, lime and other materials are used for baking during the baking process. Nitrogen blowing is prohibited in the late blowing and reduction period. Refining is carried out at a refining temperature of 1520-1540℃ and a refining time of more than 30 minutes. During the reduction period, niobium Nb should be fully reduced as much as possible to reduce losses. The steel tapping temperature is adjusted to 1560℃, and the steel is poured into the LF furnace for argon blowing to remove impurities. Samples are taken for analysis and slight adjustments are made to the chemical composition. Oxygen ≤50PPM, nitrogen ≤200PPM, hydrogen ≤5PPM, a small amount of Ni-Mg is used for final deoxidation, rare earth is added during steel tapping, and the steel tapping temperature is adjusted to 1560℃. Steel temperature 1520-1540℃, pouring electrode; 4) Electroslag processing, cutting off shrinkage holes and end flat heads, surface grinding and polishing to remove oxide scale, using argon gas protection electroslag control throughout the process, electrode welding is firm and vertical, using the exchange electrode method for production, and the delivery electrode control is completed within 2 minutes; after baking according to the system, use the purified slag system: CaF2: AL2O3: CaO: Mg = 60: 25: 10: 5 or use quaternary pre-melted slag for baking; the slag volume is about 120kg; add an appropriate amount of TiO2 powder when striking the arc, and the arc is fully slag-forming to ensure that the slag system is fully melted and the temperature is raised to 1350℃; voltage; 5 5-60V, current: 8500-9500A; control the melting rate to be uniform, the electroslag quality has no slag groove, no component segregation, and a proper amount of aluminum particles are added during the process; fully supplement the shrinkage and flatten the head in the later stage of melting, and cool it for more than 3 hours before air cooling out of the mold; 5) Homogenization treatment, the steel ingot uniformity treatment system is 1160℃, keep it warm for 24 hours, and then heat it to 1190℃ and keep it warm for 72 hours; 6) Forging processing, the steel ingot is heated below 400℃ and enters the furnace, slowly heats up to 750℃ and keeps it warm for more than 2.5 hours, and then heats up to 1240℃, keeps it warm for more than 3.5 hours to be evenly heated, the initial forging is ≥1100℃, and the final forging is ≥950℃.Tempering time is greater than 90 minutes, forging ratio is greater than 4; 100% flaw detection inspection of forged bars, removal of defect marks; 7) Hot rolling treatment, hot rolling system 1130℃-1150℃, insulation for more than 90 minutes, starting rolling temperature ≥1050℃, final rolling temperature ≥900℃; rolled bars are air-cooled, and rolling specifications are set according to requirements; 8) Heat treatment operation, solution treatment system 990℃ insulation for more than 2 hours, water cooling; 9) Machining operation, bar straightening, peeling, surface polishing, ultrasonic flaw detection; 10) Packaging, surface cleaning, mark setting, overall packaging inspection.
[0010] Beneficial effects of the present invention: The present invention is developed on the basis of existing materials. By re-adding a variety of different materials and combining them with different contents, a new material with more stable performance and various use performances better than existing alloy materials can be obtained. Corresponding technical adjustments are made on the basis of the existing rod production process, so that alloy rod products with higher quality and precision can be produced. When used in the later stage, the alloy rod products can have more reliable durability and longer service life. The processed products are of higher quality and have a wider range of uses. DETAILED DESCRIPTION
[0011] The content by weight percentage is: C: 0.04-0.05%; Si: ≤0.15%; Mn: ≤0.25%; S: ≤0.002%; P: ≤0.005%; Al: 0.250~0.75%; B: 0.003~0.035%; Cr: 17.0~21.0%; Ni: 50.0-55.0%; Mo: 2.8-3.3%; La: 0.040-0.050%; Nb+Ta:4.8-5.20%; Ti: 0.95-1.15%; Cu: ≤0.15%; O: ≤0.003%; H: ≤0.0012%; Co: ≤1.0%. Processing is carried out according to the following steps: 1) Raw material preparation, weigh the raw materials according to the proportion content and put them into the smelting container to fully bake at 800℃ for more than 4 hours, 2. The weight of the feed is greater than 20 tons; 2) Medium frequency smelting, use nickel-based materials to wash the furnace before adding the raw materials, clean the residual steel in the furnace, and smelt the prepared raw materials. Add slag deoxidation operation in the later stage of smelting, and keep the deoxidized slag gray for more than 20 minutes. The refining temperature is 1550℃, and the refining time is greater than 20 minutes. Take samples to analyze the composition and adjust it within the qualified range, increase carbon to more than C0.8%, and the steel-out temperature is greater than 1600℃. The steel-out is added into the AOD furnace; 3) AOD+LF refining, during the baking process, crystalline silicon, fluorite, lime and other materials are used for baking. Nitrogen blowing is prohibited in the late blowing and reduction period. Refining is carried out at a refining temperature of 1520-1540℃ and a refining time of more than 30 minutes. During the reduction period, niobium Nb should be fully reduced as much as possible to reduce losses. The steel-making temperature is adjusted to 1560℃, and argon is added to the LF furnace for refining to remove impurities. Sampling analysis and slight adjustment of chemical composition are carried out to detect oxygen ≤50PPM, nitrogen ≤200PPM, hydrogen ≤5PPM, and a small amount of Ni-Mg is used for final deoxidation. Rare earth is added during steel-making, and the steel-making temperature is 1520-1540℃. ℃, casting electrode; 4) electroslag processing, cutting off shrinkage holes and end flat heads, surface grinding and polishing to remove oxide scale, using argon gas protection electroslag control throughout the process, electrode welding is firm and vertical, and the production is carried out by exchanging electrodes. The delivery electrode control is completed within 2 minutes; after baking according to the system, it is equipped with purified slag system: CaF2: AL2O3: CaO: Mg = 60: 25: 10: 5 or baked with quaternary pre-melted slag; the slag volume is about 120kg; when striking the arc, add an appropriate amount of TiO2 powder, and the arc striking fully slags and makes slag to ensure that the slag system is fully melted and the temperature is raised to 1350℃; voltage; 55-60V, Current: 8500-9500A; control the melting rate to be uniform, the electroslag quality has no slag groove, no component segregation, and a proper amount of aluminum particles are added during the process; fully supplement the shrinkage and flatten the head in the later stage of melting, and cool it for more than 3 hours before air cooling after exiting the mold; 5) Homogenization treatment, the steel ingot uniformity treatment system is 1160℃, keep it warm for 24 hours, and then heat it to 1190℃ and keep it warm for 72 hours; 6) Forging processing, the steel ingot is heated below 400℃ and enters the furnace, slowly heats up to 750℃ and keeps it warm for more than 2.5 hours, and then heats up to 1240℃, keeps it warm for more than 3.5 hours to be evenly heated, the initial forging is ≥1100℃, and the final forging is ≥950℃. Tempering time is greater than 90 minutes, forging ratio is greater than 4; 100% flaw detection inspection of forged bars, removal of defect marks; 7) Hot rolling treatment, hot rolling system 1130℃-1150℃, insulation for more than 90 minutes, starting rolling temperature ≥1050℃, final rolling temperature ≥900℃; rolled bars are air-cooled, and rolling specifications are set according to requirements; 8) Heat treatment operation, solution treatment system 990℃ insulation for more than 2 hours, water cooling; 9) Machining operation, bar straightening, peeling, surface polishing, ultrasonic flaw detection; 10) Packaging, surface cleaning, mark setting, overall packaging inspection.By conducting research and development based on existing materials and by re-adding a variety of different materials and combining them with different contents, we can obtain new materials with more stable performance and various performance characteristics superior to existing alloy materials. By making corresponding technical adjustments based on the existing rod production process, we can produce alloy rod products with higher quality and precision. In the later use, they can have more reliable durability and longer service life, and the processed products can have higher quality and a wider range of use.
[0012] Preferably, C: 0.04%; Si: 0.12%; Mn: 0.25%; S: 0.002%; P: 0.005%; Al: 0.550%; B: 0.035%; Cr: 18.0%; Ni: 52%; Mo: 2.9%; La: 0.045%; Nb+Ta:4.8%; Ti: 1.15%; Cu: 0.15%; O: 0.003%; H: 0.0010%; Co: 1.0%, can reduce the overall production cost, improve the fusion efficiency between materials during production, make the density of the processed rods better, and make the performance more reliable during later use.
[0013] Preferably, C: 0.04%; Si: 0.15%; Mn: 0.15%; S: 0.002%; P: 0.002%; Al: 0.250%; B: 0.003%; Cr: 21.0%; Ni: 55.0%; Mo: 3.3%; La: 0.040%; Nb+Ta:4.8%; Ti: 0.95%; Cu: 0.11%; O: 0.001%; H: 0.0012%; Co: 1.0%, can make the hardness of the produced rod material reach the best. When it is used as raw material for the production of mechanical products in the later stage, it can make the produced products have a longer service life and more reliable durability.
[0014] Preferably, C: 0.05%; Si: 0.10%; Mn: 0.25%; S: 0.001%; P: 0.002%; Al: 0.450%; B: 0.003%; Cr: 21.0%; Ni: 55.0%; Mo: 3.1%; La: 0.045%; Nb+Ta:5.20%; Ti: 0.95%; Cu: 0.12%; O: 0.002%; H: 0.0012%; Co: 0.5%, the performance during production is relatively stable and the operation during preparation is more convenient.
[0015] Preferably, C: 0.045%; Si: 0.15%; Mn: 0.15%; S: 0.002%; P: 0.003%; Al: 0.28%; B: 0.003%; Cr: 17.0%; Ni: 50.0%; Mo: 2.8%; La: 0.04%; Nb+Ta:4.8%; Ti: 0.95%; Cu: 0.15%; O: 0.002%; H: 0.001%; Co: 1.0%. During the production of rods, bubbles are not easily generated during the fusion molding of materials during the processing, ensuring better quality during production.
[0016] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements or substitutions can be made without departing from the principles of the present invention. These improvements or substitutions should also be regarded as the scope of protection of the present invention.
Claims
1. A durable high temperature alloy bar, characterized in that: It is composed of the following elements, with the percentage by weight being: C:0.04-0.05%; Si: ≤0.15%; Mn: ≤0.25%; S :≤0.002%; P :≤0.005%; Al :0.250~0.75%; B :0.003~0.035%; Cr :17.0~21.0%; Ni: 50.0-55.0%; Mo: 2.8-3.3%; La: 0.040-0.050%; Nb+Ta:4.8-5.20%; Ti: 0.95-1.15%; Cu: ≤0.15%; O: ≤0.003%; H: ≤0.0012%; Co: ≤1.0%; the balance is iron and unavoidable impurities.
2. A durable high temperature alloy bar according to claim 1, characterized in that: C:0.04%; Si: 0.12%; Mn: 0.25%; S :0.002%; P :0.005%; Al :0.550%; B :0.035%; Cr :18.0%; Ni: 52%; Mo: 2.9%; La: 0.045%; Nb+Ta:4.8%; Ti: 1.15%; Cu: 0.15%; O: 0.003%; H: 0.0010%; Co: 1.0%.
3. The durable high temperature alloy bar according to claim 1, characterized in that: C:0.05%; Si: 0.10%; Mn: 0.25%; S :0.001%; P :0.002%; Al :0.450%; B :0.003%; Cr :21.0%; Ni: 55.0%; Mo: 3.1%; La: 0.045%; Nb+Ta:5.20%; Ti: 0.95%; Cu: 0.12%; O: 0.002%; H: 0.0012%; Co: 0.5%.
4. The durable high temperature alloy bar according to claim 1, characterized in that: C:0.04%; Si: 0.15%; Mn: 0.15%; S :0.002%; P :0.002%; Al :0.250%; B :0.003%; Cr :21.0%; Ni: 55.0%; Mo: 3.3%; La: 0.040%; Nb+Ta:4.8%; Ti: 0.95%; Cu: 0.11%; O: 0.001%; H: 0.0012%; Co: 1.0%.
5. The durable high temperature alloy bar according to claim 1, characterized in that: C:0.045%; Si: 0.15%; Mn: 0.15%; S :0.002%; P :0.003%; Al :0.28%; B :0.003%; Cr :17.0%; Ni: 50.0%; Mo: 2.8%; La: 0.04%; Nb+Ta:4.8%; Ti: 0.95%; Cu: 0.15%; O: 0.002%; H: 0.001%; Co: 1.0%.
6. The method for preparing a durable high-temperature alloy rod according to claim 1, comprising the following steps: 1) Raw material preparation: weigh the raw materials according to the proportion and put them into the smelting container to fully bake at 800℃ for more than 4 hours.
2. The weight of the raw materials is greater than 20 tons; 2) Medium frequency smelting: use nickel-based materials to wash the furnace before adding the raw materials, clean the residual steel in the furnace, and smelt the prepared raw materials. Add slag deoxidation in the later stage of smelting. The deoxidized slag is gray and white for more than 20 minutes. The refining temperature is 1550℃ and the refining time is more than 20 minutes. Take samples to analyze the composition and adjust it within the qualified range. Increase carbon to more than C0.8%, the tapping temperature is greater than 1600℃, and the tapping is added into the AOD furnace; 3) AOD+LF refining, during the baking process, crystalline silicon, fluorite, lime and other materials are used for baking. Nitrogen blowing is prohibited in the late blowing and reduction period. Refining is carried out at a refining temperature of 1520-1540℃ and a refining time of more than 30 minutes. During the reduction period, niobium Nb should be fully reduced as much as possible to reduce losses. The steel-making temperature is adjusted to 1560℃, and argon is added to the LF furnace for refining to remove impurities. Sampling analysis and slight adjustment of chemical composition are carried out to detect oxygen ≤50PPM, nitrogen ≤200PPM, hydrogen ≤5PPM, and a small amount of Ni-Mg is used for final deoxidation. Rare earth is added during steel-making, and the steel-making temperature is 1520-1540℃. ℃, casting electrode; 4) electroslag processing, cutting off shrinkage holes and end flat heads, surface grinding and polishing to remove oxide scale, using argon gas protection electroslag control throughout the process, electrode welding is firm and vertical, and the production is carried out by exchanging electrodes. The delivery electrode control is completed within 2 minutes; after baking according to the system, it is equipped with purified slag system: CaF2: AL2O3: CaO: Mg = 60: 25: 10: 5 or baked with quaternary pre-melted slag; the slag volume is about 120kg; when striking the arc, add an appropriate amount of TiO2 powder, and the arc striking fully slags and makes slag to ensure that the slag system is fully melted and the temperature is raised to 1350℃; voltage; 55-60V, Current: 8500-9500A; control the melting rate to be uniform, the electroslag quality has no slag groove, no component segregation, and a proper amount of aluminum particles are added during the process; fully supplement the shrinkage and flatten the head in the later stage of melting, and cool it for more than 3 hours before air cooling after exiting the mold; 5) Homogenization treatment, the steel ingot uniformity treatment system is 1160℃, keep it warm for 24 hours, and then heat it to 1190℃ and keep it warm for 72 hours; 6) Forging processing, the steel ingot is heated below 400℃ and enters the furnace, slowly heats up to 750℃ and keeps it warm for more than 2.5 hours, and then heats up to 1240℃, keeps it warm for more than 3.5 hours to be evenly heated, the initial forging is ≥1100℃, and the final forging is ≥950℃. Tempering time is greater than 90 minutes, forging ratio is greater than 4; 100% flaw detection inspection of forged bars, removal of defect marks; 7) Hot rolling treatment, hot rolling system 1130℃-1150℃, insulation for more than 90 minutes, starting rolling temperature ≥1050℃, final rolling temperature ≥900℃; rolled bars are air-cooled, and rolling specifications are set according to requirements; 8) Heat treatment operation, solution treatment system 990℃ insulation for more than 2 hours, water cooling; 9) Machining operations, bar straightening, peeling, surface polishing, and ultrasonic flaw detection; 10) Packaging: surface cleaning, marking and overall packaging inspection.